APPLICATION MODEL BLACK - LITTERMAN A SELECTION OF INTERNATIONAL PORTFOLIOS - Cruz Salazar, Rafael (2014)
It shows how the model Black - Litterman in building a portfolio of international assets helps improve the application of the principles on which the theory of portfolio selection proposed by Markowitz is based, allowing a more robust approach for diversified por-tfolios whose weights are modified according to the expectations that have on the performance of each of the assets. The main benefit of the model Black - Litterman is that the portfolio manager can do the analysis iteratively until a portfolio consistent with their expectations, which is an excellent alternative for those investors looking to analyze each of the elements that can influence the performance of their portfolios.